2021
DOI: 10.3390/ijms22147536
|View full text |Cite
|
Sign up to set email alerts
|

Made to Measure: Patient-Tailored Treatment of Multiple Sclerosis Using Cell-Based Therapies

Abstract: Currently, there is still no cure for multiple sclerosis (MS), which is an autoimmune and neurodegenerative disease of the central nervous system. Treatment options predominantly consist of drugs that affect adaptive immunity and lead to a reduction of the inflammatory disease activity. A broad range of possible cell-based therapeutic options are being explored in the treatment of autoimmune diseases, including MS. This review aims to provide an overview of recent and future advances in the development of cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 320 publications
(384 reference statements)
0
4
0
Order By: Relevance
“…These trials showed encouraging efficacy results, underlining the need to conduct research into new therapeutic strategies to enhance the microenvironment, which is a crucial factor to successfully induce the regeneration process [ 126 , 127 ]. In addition, the inflammatory microenvironment which is often observed in MS and SCI is unfavourable for CNS repair and can be adapted by the administration of anti-inflammatory cells such as regulatory T cells, which are currently extensively tested in the clinic [ 128 , 129 , 130 ]. These cells can be easily engineered to overexpress neuroprotective factors such as neurotrophins, thereby improving their neuroregenerative and neuroprotective properties [ 131 , 132 ].…”
Section: Discussionmentioning
confidence: 99%
“…These trials showed encouraging efficacy results, underlining the need to conduct research into new therapeutic strategies to enhance the microenvironment, which is a crucial factor to successfully induce the regeneration process [ 126 , 127 ]. In addition, the inflammatory microenvironment which is often observed in MS and SCI is unfavourable for CNS repair and can be adapted by the administration of anti-inflammatory cells such as regulatory T cells, which are currently extensively tested in the clinic [ 128 , 129 , 130 ]. These cells can be easily engineered to overexpress neuroprotective factors such as neurotrophins, thereby improving their neuroregenerative and neuroprotective properties [ 131 , 132 ].…”
Section: Discussionmentioning
confidence: 99%
“…Stem cell therapy has provided new hope for treatment of central nervous system (CNS) diseases 14–16 . In particular, mesenchymal stem cells (MSCs) have emerged as promising stem cell therapies due to their immune regulatory potential 17,18 . However, very few studies have evaluated the efficacy of MSCs for treatment of CCH induced by the 2VO approach 19 .…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] In particular, mesenchymal stem cells (MSCs) have emerged as promising stem cell therapies due to their immune regulatory potential. 17,18 However, very few studies have evaluated the efficacy of MSCs for treatment of CCH induced by the 2VO approach. 19 Moreover, donor heterogeneity of primary MSCs is a major hurdle to clinical use.…”
Section: Introductionmentioning
confidence: 99%
“…More applied applications of primary lung tissue samples include the development of epithelial culture models for optimization of either cell-or gene-based corrective therapies. Cell-based therapies have been adopted for diseases involving a variety of organs and cell types [19][20][21][22][23][24][25][26][27][28][29][30][31], and in combination with therapeutic gene correction of long-lived lung epithelial progenitors, may represent a plausible approach for monogenic lung diseases such as cystic fibrosis [32][33][34]. However, realization of stem cell-based therapeutic approaches for lung regenerative medicine will require development and validation of reproducible protocols allowing standardization and scalability, as has been demonstrated in other tissues [35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%